التناذر الصدمي عند المتعافين من مضاعفات كوفيد-19 المستجيبين للعلاج الأكسجيني - بوشيخي سميرة; رحال سامية (University of Eloued جامعة الوادي, 2023)
Abstract: The current study aimed to explore the severity of symptoms of the traumatic syndrome among those recovered from complication of Covid-19 virus who responded to oxygen therapy during the hospitalization process (respiratory distress syndrome as a model) on a sample of 62 patient where they were in a real confrontation with death in the state of Mostaganem, and the differences in the severity of this traumatic syndrome according to the gender variable. To find out, we relied on, the descriptive approach and PSSI-5 scale. The result showed that there were severe symptoms of traumatic syndrome, so cognition and mood syndrome appeared in the first place, the re-experiencing syndrome in the second place, then the arousal and avoidance syndrome. The study also revealed that there were no differences in the severity of traumatic syndrome due to the gender variable. هدفت الدراسة الحالية إلى الكشف عن شدة أعراض التناذر الصدمي الأكثر ظهوراً عند المتعافين من مضاعفات كوفيد-19 الذين استجابوا للعلاج الأوكسجيني خلال عملية الاستشفاء (متلازمة الضائقة التنفسية كنموذج) عند عينة متكونة من 62 شخص أين كانوا في مواجهة حقيقية مع الموت بولاية مستغانم مع معرفة الفروق في شدة هذا التناذر الصدمي وفقاً لمتغير الجنس. ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي بالاعتماد على مقياس أعراض اضطراب الضغط ما بعد الصدمة PSSI-5، حيث أشارت نتائج الدراسة إلى وجود أعراض تناذر صدمي شديدة فظهرت أعراض تناذر تغيرات الإدراك والمزاج في المرتبة الأولى ثم تناذر إعادة الخبرة في المرتبة الثانية ثم يليه أعراض فرط الإثارة والتجنب. كما كشفت الدراسة عن عدم وجود فروق في شدة التناذر الصدمي تُعزى لمتغير الجنس.
Keywords: صدمة نفسية; تناذر صدمي; كوفيد-19; علاج أوكسجيني; psychological trauma; traumatic syndrome; Covid-19; oxygen therapy